Do Service Quality, Price, and Location affect on Customer Satisfaction in Kampoeng SPA, Sumenep? - Ningsih, Rasmiati; Kurdi, Moh (SAN Scientific, 2023)
This study aimed to determine the effect of service satisfaction, price, and location on customer satisfaction. The type of examination is quantitative exploration, with the client population of Kampoeng SPA in the Sumenep, Madura. The testing strategy in this exploration is a purposive testing method. Information was collected using surveys, interviews, perception, and documentation methods. The information tests used are Illustrated Insights, Exploration Instrument Tests, Traditional Assumptions Tests, Tests for Various Straight Relapse Conditions, and Suitability Tests. The results of this study indicate that the quality, cost, and extent of consumer loyalty in Kampoeng SPA as a whole affect consumer loyalty in Kampoeng SPA. Judging from the t-test shows that the administrative quality factors, costs, and area as a whole influence consumer loyalty. This research can be a benchmark for Kampoeng SPA in the Sumenep Regime to retain consumers to buy their products. The success of Kampoeng SPA employees and owners in the Sumenep Regime in determining prices, selecting locations, and providing service forms following consumer wants and needs and satisfying consumers